Reptilia, Chelonii, Chelidae, Phrynops geoffroanus Schweigger, 1812 and Mesoclemmys vanderhaegei (Bour, 1973): distribution extension, new country record, and new province records in Argentina - Baldo, Juan Diego (2007)
The Chelonii is currently represented in Argentina by 14 species of 10 genera, belonging to six families (Richard and Waller 2000). Although several authors have addressed the study of Argentinean turtle species (e.g. Freiberg 1938; 1977; Cei 1993; Cabrera 1998; Richard 1999; Richard and Waller 2000), the knowledge about natural history and geographic distribution of some species is still fragmentary. One of these poorly known species is the freshwater turtle Phrynops geoffroanus. This turtle is widely distributed in South America eastern to the Andes, in the Orinoco, Amazonas, São Francisco, and Paraná rivers basins (Iverson 1992; Souza 2005). Bertoni (1925) recorded the presence of P. geoffroanus (as Hydraspis geoffroyana) at the locality of Puerto Bertoni in the High Paraná River, Paraguay, and suggested that it was likely to occur in northeastern Argentina, in the province of Misiones; subsequently Freiberg (1938; 1970; 1977) reported the presence of P. geoffroanus in the province of Misiones. Rhodin and Mittermeier (1983) described Phrynops williamsi and mentioned the presence of this species in the Misiones, within the distribution range of P. geoffroanus. This was accepted by other authors, who suggested that P. geoffroanus was present in Argentina (Pritchard and Trebbau 1984; Ernst and Barbour 1989; Iverson 1992; Fritz and Havas 2007). Nevertheless, most of recent studies about the Argentinean turtle fauna excluded P. geoffroanus from it, based on the absence of specimens in collections, and also because previous reports were considered to be misidentification records of P. williamsi (Waller and Chebez 1987; Richard et al. 1990; Cei 1993; Cabrera 1998; Richard 1999; Richard and Waller 2000).